2020
DOI: 10.3390/pharmaceutics12100932
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Design of Sustained-Release Tablet Garcinia cambogia Extract and Bioconverted Mulberry Leaf Extract for Anti-Obesity

Abstract: Obesity is a major health concern worldwide, and it is leading to worsening disease morbidity and mortality. Herbal supplements and diet-based therapies have attracted interest in the treatment of obesity. It is known that Garcinia cambogia (GA) and mulberry leaf, which contain polyphenols, have anti-obesity activity. Herein, we developed a combined tablet consisting of GA extract and bioconverted mulberry leaf extract (BMUL) using a statistical design approach. The ratio and amount of sustained polymers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Network pharmacology is an emerging discipline that is based on the statistical analysis of data, virtual computing and the observation of component-target-disease-pathway interactions retrieved from network databases (23). MLE have been previously demonstrated to alleviate hyperglycemia, hyperlipidemia, obesity, oxidation and inflammation (24)(25)(26)(27)(28). Pharmacological analysis has indicated that the active components in MLE include β-carotene, quercetin, β-sitosterol, kaempferol and arachidonic acid, all of which can exert beneficial effects against obesity (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is an emerging discipline that is based on the statistical analysis of data, virtual computing and the observation of component-target-disease-pathway interactions retrieved from network databases (23). MLE have been previously demonstrated to alleviate hyperglycemia, hyperlipidemia, obesity, oxidation and inflammation (24)(25)(26)(27)(28). Pharmacological analysis has indicated that the active components in MLE include β-carotene, quercetin, β-sitosterol, kaempferol and arachidonic acid, all of which can exert beneficial effects against obesity (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, G. cambogia and G. indica were found to contain the highest (−)-HCA and its lactone levels, and suggestive that G. indica can be used instead of G. cambogia especially if targeting its HCA. Likewise, (−)­hydroxycitric acid was analyzed in G. cambogia commercial samples using HPLC/UV. , The mean recovery of HCA from G. cambogia extracts ranged 98.4–100.5% with coefficients of variation of 0.25–0.63% and accuracy range of 2–10 μg, reflecting that the method is validated for the routine analysis of HCA in commercial G. cambogia extracts . The method also offered selectivity compared to traditional acid base titration methods which quantify for total acids, not only targeting HCA .…”
Section: Introductionmentioning
confidence: 95%
“…The use of different types of polymers to control the drug release process represents one of the main aspects of the development of different types of matrix systems. Hydrophilic matrices are often the first choice in the development of modified-release pharmaceutical forms [10][11][12]. They are usually monolithic systems containing one or more hydrophilic polymers [13].…”
Section: Introductionmentioning
confidence: 99%